Panel Quantile Approach towards Exigent Determinants of Food Security in the Selected Developing Countries - Hafiz Asim; Rehman, Hafeez ur (Pakistan Journal of Humanities and Social Sciences, 2024)
This paper presents the comprehensive measurement of food security index by incorporating all of its dimensions for a panel of 50 developing countries. The study also empirically examines the exigent determinants of the overall food security index across developing countries by categorizing them into two distinct income groups from 2007 to 2020. The study used Panel Quantile Regression to capture and analyze the heterogeneous effects across different quantiles of the distribution. The findings reveal that urbanization, food prices, and unemployment negatively affect food security, whereas the effect of unemployment is obscure as the country’s income rises. Findings also indicate that carbon emissions may pose a significant threat to food security in newly industrialized countries. Furthermore, the findings also illustrate that GDP per capita, literacy rate, arable land, credit to agriculture, and institutional quality are significant contributors to food security. Hence, there should be a significant emphasis on improving the quality of institutions to strengthen the positive determinants of food security and mitigate their adverse effects.